Building a Low-Cost Lora Gateway based on .Net Core for Fast Development and Easy Integration - Haryono (The Indonesian Journal of Computer Science, 2023)
In the world of IoT, it is involving many devices, each Node needs to send/receive the data from/to Datacenter. The Lora Gateway is usually used to achieve that communication. There are many ways to implement the Lora Gateway, it may use available Lora Gateway in the market. This method may be faster but need to have an extra fee, especially when many gateways are needed. Another method is by using the available GSM Network Gateway, this may lead fast but require managing Simcard at each Node. Both are less flexible as the data format needs to follow according to the standard of the Gateway which is chosen. Some methods select to build the Lora Gateway by themself, but this requires some development and integration that leads to giving extra time. To compensate above problem this project is involved. The aim is to prove, that it is possible to build a Low-Cost Lora Gateway based Time Division with the help of on .Net Core prgramming. As of today .Net Core can run in the Linux OS environment smoothly, hence building Lora Gateway based Time Division using on .Net Core is very possible to be done. By developing for all devices using .Net Core the communication data across the device is easy to achieve. It is because all projects in each device reference the same library that contains the same data entities and services. This project proves that building a Low-Cost Lora Gateway based on .Net Core is successfully done. The development and integration are relatively easy and fast. The fee to build the Lora Gateway is less compared to using available Gateway in the market or using GSM Gateway.